Strategi Pembelajaran Bahasa Indonesia Berbasis Discovery Learning dan Podcast: Relevansi Filsafat Pendidikan dalam Meningkatkan Kompetensi Menceritakan Kembali - Ma'rifi, Hisyam; Suhartono; Ahmadi, Anas; Indrawati, Dianita (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
The development of information and communication technology in the digital era has significantly influenced language use patterns among students. One linguistic phenomenon emerging from this transformation is bahasa plesetan (wordplay), a modified form of language used to create humor, satire, or creative expression. This study aims to analyze the forms and characteristics of bahasa plesetan used by students in the digital era, examine its influence on language literacy skills, and formulate effective learning strategies to balance linguistic creativity with mastery of standard language. This research employs a qualitative descriptive approach using a library research method. Data were obtained from various academic sources and analyzed through content analysis to interpret the linguistic patterns and sociocultural meanings embedded in the phenomenon of bahasa plesetan. The findings reveal that bahasa plesetan serves dual functions: as a medium of creative expression and as a representation of students’ social identity in digital spaces. While it enriches linguistic creativity, it also risks diminishing sensitivity to formal language norms if not accompanied by adequate digital literacy and proper guidance. Therefore, Indonesian language learning should integrate contemporary linguistic phenomena such as bahasa plesetan into reflective and contextual pedagogical strategies to strengthen students’ language literacy in the digital era.